PERCEPTIONS OF PARENTS AGAINST GIRLS HIGHER EDUCATION IN JORONG (STUDY ON SOCIETI IN JORONG TAMPUS NAGARI UJUNG GADING KECAMATAN LEMBAH MELINTANG KABUPATEN PASAMAN BARAT - Maria Ulfa; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in Jorong Tampus Kecamatan Lembah Melintang Kabupaten Pasaman Barat. The purpose of this study was to analyze the perceptions of parents towards the education of girls. The research titled “Perceptions of Parents Against Girls Higher Education in Jorong Tampus Kecamatan Lembah Melintang Kabupaten Pasaman Barat”. Topics focus of this research is how the perception of parents towards the education of girls in Jorong Tampus Kecamatan Lembah Melintang Kabupaten Pasaman Barat. Respondents are parents who have daughters and are not authorized continuing education. The sample in this study amounted to 37 people. The author uses descriptive quantitative method and the data were analyzed quantitatively and using sampling techniques rendom simple decision. Instruments of data are observations, questionnaires and documentation. From research conducted, Respondent perception of the education of girls in JorongTampus on is assumed that the right to education for girls are able to change the pattern of thought with the percentage as much as 78.3%. This means that parents and respondents in JorongTampus accept the assertion that higher education is important for girls. From what is happening in the field in accordance with the results of the processed data, that society. However, despite being aware that higher education is important to be able to change the mindset of daughters still respondents felt that higher education opportunities for girls are not so important that characterized the percentage as much as 48.6%. Factors that influence the perception of parents and respondents to the higher education of girls in JorongTampus is, the view parents who think girls are better incorporated into skills training such as courses with a percentage of the election as much as 75.7%.Keywords: Perception, Education, Women's Educati